2013
DOI: 10.1371/journal.pone.0063378
|View full text |Cite
|
Sign up to set email alerts
|

Epiblast Ground State Is Controlled by Canonical Wnt/β-Catenin Signaling in the Postimplantation Mouse Embryo and Epiblast Stem Cells

Abstract: Epiblast stem cells (EpiSCs) are primed pluripotent stem cells and can be derived from postimplantation mouse embryos. We now show that the absence of canonical Wnt/β-catenin signaling is essential for maintenance of the undifferentiated state in mouse EpiSCs and in the epiblast of mouse embryos. Attenuation of Wnt signaling with the small-molecule inhibitor XAV939 or deletion of the β-catenin gene blocked spontaneous differentiation of EpiSCs toward mesoderm and enhanced the expression of pluripotency factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 53 publications
9
111
0
Order By: Relevance
“…Homogenous primed-state mEpiSC lines can be more efficiently established in the presence of Wnt inhibitors, such as IWP2 (42) and XAV939 (43). Our mass spectrometry-based analysis of protein expression profiles of naïve ELF1 hESCs with inhibition of Wnt/ β-catenin signaling also suggests that blocking of Wnt/β-catenin signaling could lead naïve hESCs to a more primed-like state (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Homogenous primed-state mEpiSC lines can be more efficiently established in the presence of Wnt inhibitors, such as IWP2 (42) and XAV939 (43). Our mass spectrometry-based analysis of protein expression profiles of naïve ELF1 hESCs with inhibition of Wnt/ β-catenin signaling also suggests that blocking of Wnt/β-catenin signaling could lead naïve hESCs to a more primed-like state (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Although the effect of Wnt signaling in iNOS-induced drug resistance was confirmed in our experiment, the differences between canonical and noncanonical Wnt pathways in regulating the level of iNOS were still unclear. By treatment with Wnt/β-catenin inhibitor XAV939 (18,19), Wnt/Ca 2+ inhibitor XeC (20,21) and Wnt/JNK inhibitor SP600125 respectively in A549/CDDP, we found a lower iNOS and GST-π, and a higher TOPO IIα in the Wnt/β-catenin-blocking group. However, neither Wnt/JNK nor Wnt/Ca 2+ pathway were correlated with iNOS, GST-π and TOPO IIα as shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…4A). Next, we established EpiSCs from E6.5 embryos using N2B27-based medium supplemented with activin A, basic fibroblast growth factor and the Wnt signalling inhibitor, XAV939 (Sumi et al, 2013) and confirmed that the established cells were in a primed state by examining several markers; alkaline phosphatase staining confirmed that signals in EpiSCs were weaker than in ESCs (Fig. S4A).…”
Section: /Hprtmentioning
confidence: 75%